1997
DOI: 10.1148/radiology.205.3.9393521
|View full text |Cite
|
Sign up to set email alerts
|

PTFE-encapsulated endovascular stent-graft for transjugular intrahepatic portosystemic shunts: experimental evaluation.

Abstract: This PTFE-encapsulated stent-graft is biocompatible and safe to place. It markedly improves TIPS patency, providing almost uninterrupted, unimpeded patency in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 0 publications
2
43
1
2
Order By: Relevance
“…In addition, they emphasize the feasibility and efficacy of PTFE-covered stents used not only for de novo indications but also for the correction of TIPS dysfunction in patients with severe clinical recurrence. 26,30,32 Importantly, it should be noted that no Budd-Chiari patient in this series who was treated with a PTFE-covered stent developed liver infarcts. Liver infarcts have been reported after PTFE stents in patients with liver cirrhosis and are due, in most cases, to the obstruction of the hepatic vein by the covered stent.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, they emphasize the feasibility and efficacy of PTFE-covered stents used not only for de novo indications but also for the correction of TIPS dysfunction in patients with severe clinical recurrence. 26,30,32 Importantly, it should be noted that no Budd-Chiari patient in this series who was treated with a PTFE-covered stent developed liver infarcts. Liver infarcts have been reported after PTFE stents in patients with liver cirrhosis and are due, in most cases, to the obstruction of the hepatic vein by the covered stent.…”
Section: Discussionmentioning
confidence: 75%
“…Accordingly, understanding the predisposing factors leading to TIPS dysfunction and efforts to solve those problems are necessary to maintain long-term patency after TIPS placement. Currently, the best solution for TIPS dysfunction seems to be the use of polytetrafluoroethylene-covered stent grafts that isolate blood from hepatic tissue, therefore blocking the tentative triggering mechanisms of pseudointimal and intimal hyperplasia or thrombosis (19)(20)(21)(22)(23)(24)(25)(26)(27). Recently, a meta-analysis of six studies demonstrated not only a significant improvement of primary patency (hazard ratio [HR], 0.28) and a significant reduction of risk of hepatic encephalopathy (HR, 0.65), but also a significant decrease of mortality in the covered-stent group (HR, 0.76) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Among many theories, widely accepted ones are thrombosis, pseudointimal hyperplasia caused by bile leaks of transected bile ducts into the stent lumen, and intimal hyperplasia of the hepatic vein outflow tract (16)(17)(18). Recently, use of polytetrafluoroethylene (PTFE)-covered stents has decreased TIPS dysfunction by allowing endoluminal endothelial lining and preventing bile leak into the stent (19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The stentgraft has also been used to treat hemorrhage after extrahepatic portal vein puncture during a TIPS procedure [16]. Several graft materials have been used for construction of stent-grafts [8][9][10]. The Viatorr stent-graft (W L Gore, Flagstaff, AZ, USA) used in our study is a nitinol-polytetrafluoroethylene stent-graft for TIPS, commercially available and easy to handle [17].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these problems, stent-grafts have been used [7][8][9][10][11][12]. These stent-grafts separate the shunt channel from the liver tissue, bile ducts, and the wall of the hepatic vein, preventing development of hyperplasia.…”
Section: Introductionmentioning
confidence: 99%